Translating Baby Tuckoo: Portraits of the Artist as a Very Young Man - O'Neill, Patrick (ABEI Journal, 2016)
A comparative reading across several different languages of the opening sentences of Joyce’s text suggests the possible interpretive implications of a macrotextual Portrait.Keywords: translation effects; transtextual reading; texts and macrotexts.